Prospects for the development of legal regulation of the crypto currency market in Russia - O. I. Larina (E-Management)
An accomplished fact is the development of the cryptocurrency market, including in Russia. At the same time, the Russian legal regulation mechanism has not yet been formed, and the existing draft law on the circulation of digital financial assets has not yet been agreed. Growing demand for cryptocurrencies from investors carries systemic risks, as well as threats of using digital financial assets for illegal purposes. In this regard, regulators in different countries are forced to take measures to legislate the circulation of such assets. At the same time, such measures can be quite different: from simply informing subjects about possible risks to the adoption of detailed laws establishing the rules for the circulation of such assets, the rights and obligations of subjects. At the same time, country approaches not only to regulation, but also to the definition of the essence of cryptocurrencies (money, assets, rights) differ greatly.The purpose of the article is to form recommendations on possible development of directions of Russian regulation of the cryptocurrency market. International approaches to the regulation of digital currencies, the practice and features of their application, as well as the proposed legal norms of the Russian bill on the use of digital financial assets in civil circulation have been analyzed in the article. As the research methodology, legal and comparative analysis of Russian and foreign practice has been used. Recommendations for making amendments to the current financial legislation and emerging digital legislation have been given. According to the author, the development of the cryptocurrency market in Russia in the near future will be influenced by the following facts: the adoption of digital legislation, international experience and practice of using cryptocurrencies, technological changes.